The inhibitory effect of boric acid on hypoxia-regulated tumour-associated carbonic anhydrase IX - Zainab Saad Yusuf; Tugba Kevser Uysal; Ender Simsek; Alessio Nocentini; Sameh Mohamed Osman; Claudiu T. Supuran; Özen Özensoy Güler (Taylor & Francis Group, 2022)
Carbonic anhydrases (EC 4.2.1.1) catalyse the reversible hydration of CO2 into bicarbonate and protons. As a hypoxia-sensitive and tumour-associated isoform, isoform CA IX, is significantly overexpressed in various malignancies, being a validated target for new anticancer/antimetastatic drugs. A multitude of studies has shown that CA IX inhibition decreases cancer cell proliferation and metastasis through pHe/pHi modulation and enhancement of ferroptosis among others. Numerous studies demonstrated increased efficacy of cytotoxic drugs combined with CA inhibitors (CAIs) in various cancer types. We tested the inhibitory effect of boric acid (BA), an inorganic Lewis acid, on CA IX as well as other isoforms (CA I, II, and XII). BA acted as a millimolar in vitro CAI, decreased proliferation of two cancer cell lines, although not strong correlations between the in vitro inhibition and in vivo effects were observed. The mechanism of antiproliferative action of BA should be investigated in more detail.